Exploring the role of moderators in the effectiveness of digital games for stem education: a systematic review and meta-analysis - Isnanik Juni Fitriyah; Sony Yunior Erlangga; Andik Wahyun Muqoyyidin; Septi Aprilia (Discover Education)
Abstract Research on the possible benefits of digital games for learning outcomes in STEM education has shown mixed results, which is another reason that this study is focused on inconsistencies in past research outcomes. Moreover, it seeks to explore the moderator variables which affect the success of digital games like game design, interactive technology, duration of intervention, and country status and identify the most influenced learning outcomes. To date, no prior meta-analysis has explored this topic, making this systematic literature review (SLR) and meta-analysis the first of its kind in the field as of 2024, leading to the analysis of 44 studies (N = 3861) published between 2014 and 2024. Methods: Data were gathered through six databases, and inclusion criteria consisted of digital game-based intervention studies with experimental and control groups. Data were analyzed using effect sizes (SMD), heterogenicity and moderators. Digital Games did have a strong positive impact on STEM learning outcomes (SMD = 1.26). Through dominance moderators including game design, intervention time, nationals, and subject focus, the most significant effects were demonstrated on problem solving abilities, critical thinking and learning motivation. Though shorter intervention duration yielded smaller effects, more sophisticated technology like AR/VR, and inquiry-based learning models had all managed the best effects. The above research also makes a mark by showing how moderator variables such as country status technology and game design influence digital game-based STEM learning outcomes. These findings are important to inform game-based learning design amongst educators, curriculum developers, and policymakers, particularly in how to design effective interventions that address the goal of access using technology in developing countries.